Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I would like to rewrite the sum

$$\sum_{i=1}^K \sum_{l=-\infty}^\infty \sum_{j=-\infty}^\infty f(i+lK;j-l)$$ In the form

$$ \dots\sum_{s=-\infty}^\infty \sum_{w=-\infty}^\infty f(s,w)$$ where $s=i+lK$, $w=j-l $. How do I do it?

share|cite|improve this question
In what sense does the original sum converge? (I can imagine three possibilities: absolutely, conditionally, as a principal value). – user31373 Jun 20 '12 at 17:57
The sum convergence absolutely – Katja Jun 20 '12 at 18:02
up vote 2 down vote accepted

I think that the sum is exactly $$\sum_{s=-\infty}^\infty \sum_{w=-\infty}^\infty f(s,w)$$ Indeed, consider an ordered pair $(s,w)\in\mathbb Z\times\mathbb Z$. The integer $s\in \mathbb Z$ has a unique representation $s=i+lK$ for some $i\in\{1,\dots,K\}$ and $l\in\mathbb Z$. Since $l$ is already determined, from $w=j-l$ we get $j=w+l$. Thus, $(s,w)$ appears in the original sum exactly once.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.